“La pomada de azahar como alternativa de la medicina tradicional y su efecto en el alivio de malestares musculares de los trabajadores de la municipalidad distrital de morales” - Castillo Santa María, Inés (2014)
This research entitled "thé ointment of orange blossom as alternative of traditional medicine and its effect in relieving muscular discomfort of workers of the municipality district of Morales", purpose was to determine the effect of ointment of orange blossom as an alternative to traditional medicine in relieving muscular discomfort of workers in the district municipality of Morales 2014. According to its objective is experimental design experimental pre; According to your measurement is quantitative and seeks to determine the effect of the · independent variable on the dependent variable. The sample used was made up of 20 people, selected with a sampling non probability, i.e. taken by convenience of researchers, who applied the pre and posttest through a data collection instrument, the same as it was validated with the technical experts with specialists in the field. The result of this research is favorable in ternis of the effect that produces orange blossom ointment as alternative to traditional medicine; since it contrasted; the hypothesis where evidenced statistically than the ointment of orange blossom had a significant effect in relieving the muscular discomforts of workers of the municipality of the District of Morales ..